International survey of audiologists during the COVID-19 pandemic: use of and attitudes to telehealth. - Eikelboom, Robert H.; Bennett, Rebecca J.; Manchaiah, Vinay; Parmar, Bhavisha; Beukes, Eldré; Rajasingam, Saima L.; Swanepoel, De Wet (International Journal of Audiology, 2022)
To determine the attitudes of audiologists towards telehealth and use of telehealth for the delivery of ear and hearing services pre-, during- and post- the COVID-19 pandemic, and to identify the perceived effects of telehealth on services and barriers to telehealth. An online survey distributed through the International Society of Audiology and member societies. A total of 337 audiologists completing the survey between 23 June and 13 August 2020. There was a significant increase in the perceived importance of telehealth from before (44.3%) to during COVID-19 (87.1%), and the use of telehealth previous (41.3%), current (61.9%) and expected use of telehealth (80.4%). Telehealth was considered adequate for many audiology services, although hearing assessment and device fitting by telehealth received least support. Matters related to timeliness of services and reduction of travel were reported as the main advantages, but relationships between practitioners and clients may suffer with telehealth. Important barriers were technologies related to the client or remote site; clinic-related items were moderate barriers, although more clinician training was a common theme provided through open-ended responses. The COVID-19 pandemic has resulted in audiologists having a more positive attitude towards and greater use of telehealth, but with some reservations.